Diversity of Macrosscopic Fungi in the Cibereum Waterfall Path, Mount Gede Pangrango National Park (TNGGP) West Java - M. Fihris Yafa; Ardyan Pramudya Kurniawan; Arifah Khusnuryani (Jurnal Biologi Tropis, 2022)
Indonesia is a tropical country that has natural resources that are rich in biodiversity. One of these biodiversity is mushrooms. Mushrooms generally occupy various types of habitats, namely soil, wood, litter, animal waste and some grow on rotting mushrooms.. This study aims to study the diversity of Microscopic Fungi in the Cibereum Curug Route,Selabintana Resort, Gunung Gede Pangrango National Park, West Java. The research method used in this study is VES (Visual Encounter Survey) by combining transects following the Cibereum waterfall path, and taking the right and left areas of 1 meter. Data analysis was performed by qualitative descriptive analysis and quantitative descriptive analysis. The results of the research on the Curug Cibereum Resort Selabintana route, Gunung Gede Pangrango National Park (TNGGP) West Java, found as many as 30 species of basidiomycota mushrooms and 3 species from the ascomycota division. The most common species found in the study area were Coprinellus disseminatus (336 Number of individuals/4000 m2), Stereum sp (153 Number of individual/ 4000 m2), Mycena roseignicola (145 individual pieces/4000 m2), and Favolaschia pustulosa (138 Number of individual / 4000 m2). The diversity index of basidiomycota fungi in the Curug Cibereum route is in the medium category, namely H'= 1.004.